2016
DOI: 10.1039/c6ra14667h
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the preparation of Ni–CeO2 composite cathodes with enhanced electrocatalytic activity

Abstract: In this work, supergravity fields were utilized to prepare Ni-CeO 2 composite cathodes from a nickel sulphamate bath containing suspended nano-sized CeO 2 particles. The prepared Ni-CeO 2 composite coatings exhibit a significant enhancement in electrocatalytic activity for the hydrogen evolution reaction (HER) in alkaline solutions. The crystal structure, morphology and chemical compositions of the composite coatings were characterized by XRD, SEM and EDS measurements. It was shown that the prepared Ni-CeO 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The value of (R ct + R p ) could also explain electrocatalytic activity for HER which have studied in our published papers. 18,20 Considering electrochemical active surface area plays a crucial role in improving electrocatalytic activity for HER, the surface roughness R f is calculated by comparing the double layer capacitance C dl value with 20 mF cm À2 for smooth electrode surface (R f ¼ C dl /20). 44 The double layer capacitance C dl of the electrode is obtained by using the equation from Brug et al 10,[46][47][48][49] As calculated in Table 3, it can be found that the R f values of Ni-rGO composite samples increase remarkably compared with the pure Ni electrode, and obtain the highest value of 836 for 0.7 g L À1 GO in bath solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of (R ct + R p ) could also explain electrocatalytic activity for HER which have studied in our published papers. 18,20 Considering electrochemical active surface area plays a crucial role in improving electrocatalytic activity for HER, the surface roughness R f is calculated by comparing the double layer capacitance C dl value with 20 mF cm À2 for smooth electrode surface (R f ¼ C dl /20). 44 The double layer capacitance C dl of the electrode is obtained by using the equation from Brug et al 10,[46][47][48][49] As calculated in Table 3, it can be found that the R f values of Ni-rGO composite samples increase remarkably compared with the pure Ni electrode, and obtain the highest value of 836 for 0.7 g L À1 GO in bath solution.…”
Section: Resultsmentioning
confidence: 99%
“…Among the non-noble metals, Ni and Ni-based electrode materials have been widely considered as promising electrocatalytic materials due to their comparatively large electrocatalytic activity and good stability for HER in alkaline solutions. 8 Two main approaches including alloying Ni with some other metals or non-metals [9][10][11][12][13][14][15][16] and compositing Ni with active nano-sized particles [17][18][19][20][21][22] have been taken to enhance the intrinsic activity and/or increase the real surface area of electrode materials for HER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al studied the effects of different magnitudes of CeO 2 on Ni-S and Ni-Zn coatings in the catalytic activities of HERs [23,24]. Our team studied the catalytic activities of Ni-CeO 2 and Ni-S/CeO 2 composites in hydrogen evolution [27,28]. In this paper, we prepared different morphologies of CeO 2 and studied the impacts of different CeO 2 morphologies on Ni-S alloys in HERs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, CeO 2 has been extensively studied for catalytic application owing to its high oxygen transfer ability. Considering the morphology and surface structure‐dependent catalytic properties of CeO 2 , the size and shape‐controlled synthesis of CeO 2 micro‐/nanocrystals has been a matter of intense research . However, owing to the existence of a highly exposed surface, the CeO 2 nanoparticles tend to aggregate and thus lower the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%